The effect of one-night sleep dprivation on pacing strategies and intermittent-sprint performance - Skein, M.; Didffield, R.; Mundell, T.; Edge, J.; Short, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Sleep deprivation prior to team sport exercise may result from a variety of reasons, including travel commitments and anxiety; however the ensuing effects on performance and recovery remain equivocal. Therefore, the aim of this study was to examine the effect of overnight sleep loss (~30hrs) on pacing strategies and performance for intermittent-sprint exercise. Methods: Seven male, team sport athletes completed a familiarisation session, including a graded exercise test to determine VO2peak, and two conditions consisting of 2 consecutive days each including a 30min graded exercise run at 60-80% VO2peak followed by a 50min free-paced intermittent-sprint protocol (ISP). Each day was separated by either a normal night sleep (CONT) or an absence of sleep (SDEP). The ISP consisted of a 15-m sprint each minute followed by self-paced exercise in a shuttle run format at varying intensities (hard running, jogging, walking and bounds) for the remainder of each minute. Each day, pre and immediately post exercise, 15 maximal voluntary contractions (MVC) with a resting (Pf) and superimposed (SIF) twitch on the first and final 5 MVC of the right knee extensors were assessed. Pre and post exercise muscle biopsies were obtained from the vastus lateralis and assessed for muscle glycogen. Heart rate (HR), core temperature (Tcore), blood lactate (La) and glucose (Glu), and Rating of Perceived Exertion (RPE) were recorded throughout, while Profile of Mood States (POMS) was completed pre and post exercise. Results: Sprint times were reduced on Day2 compared to Day1 within both conditions (P<0.05) however a greater reduction was evident within SDEP. Distance covered during self-paced exercise was negatively affected in SDEP Day2 compared to Day1, with a lower total distance during hard running bouts (P<0.05); however no significant differences were evident within the CONT condition. Mean distance covered during bounds was also lower in SDEP (P<0.05). Muscle glycogen was significantly lower pre exercise on Day2 following SDEP compared to CONT. Blood La and Glu were lower on Day2 in both conditions compared to Day1 (P<0.05). RPE and POMS were also adversely affected by sleep loss compared to Day1 (P<0.05). Finally, MVC, SIF & VA pre exercise on Day2 were significantly lower during SDEP compared to CONT (P<0.05). Discussion: Results indicate that the ISP was negatively affected by ~30h sleep deprivation, through the reduction in self-selected exercise intensities (pacing strategies). Further, sleep loss retards the repletion of muscle glycogen and may be responsible for the greater decline in performance on the second day. Accordingly, the reduction in muscle glycogen and increased psychological strain prior to exercise may result in the reduction of voluntary muscle recruitment noted in MVC and thus be responsible for the slower pacing strategies and reduced performance noted following sleep loss.